PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK BERBASIS PROBLEM BASED LEARNING PADA MATERI SISTEM PERSAMAAN LINEAR DUA VARIABEL UNTUK KELAS VIII SMP - Ridwan Amnur (Jurnal Edukasi dan Penelitian Matematika, 2020)
This study aims to develop PBL-based LKPD on the material of Two-Variable Linear Equation System for Class VIII SMP. The research design used the Ploom model which consisted of three stages, namely preliminary research, the development / prototyping stage, and the assessment stage. In the preliminary research, needs analysis, curriculum analysis, concept analysis and student analysis were carried out to see the LKPD relationship to be developed. At the development / prototype stage, a PBL-based LKPD was made based on the analysis that was carried out in the previous stage. The prototype must perform a formic evaluation in the form of self-evaluation and expert evaluation to produce a valid prototype. The assessment phase aims to see the practical prototype after the one to one evaluation is carried out. This research is limited to evaluation stage one because of the Covid-19 outbreak. The conclusion from this research is that the PBL-based LKPD on the material of the Two-Variable Linear Equation System is valid and practical. Keywords — Development Research, Problem Based Learning, Two-Variable Linear Equation System.